Quality of Work Life of the Administrative Technical Servants in Education: Analysis of a Brazilian Federal University - Siqueira, Paulo Henrique de Lima; Teodoro, Bernardo Cintra; Bertassi, André Luiz (Archives of Business Research, 2020)
The New Public Management has incorporating private business administration precepts that aim to optimize the public service provision. This model has done the stability of public office more flexible through performance evaluation. So the objective of this study was to know and to evaluate the Quality of Work Life perceptions of the administrative technical servants in education in a Brazilian Federal University. The target population was 540 activity administrative technical servants in education at the Federal University of São João del-Rei, Minas Gerais. Of the 176 respondents, 62.50% were married or in a stable relationship, 93.85% have at least completed Higher Education, totaling 168 individuals, what justify the health services, social assistance and extra benefits dissatisfied by the interviews because they need to support and afford personal and family health. Neutrality / dissatisfaction trends were found in the aspects like personal and professional development, task variety and growth opportunity. It happened because 92% of the respondents have a higher level of education than the job requirement. For the university, it is suggested to include measures to improve people management that involve working methods, autonomy in the execution of tasks, access to commissioned functions and greater participation in decisions regarding tasks.